2019
DOI: 10.1038/s41598-019-49383-8
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a Kavain Analog with Efficient Anti-inflammatory Effects

Abstract: Kavain, a compound derived from Piper methysticum, has demonstrated anti-inflammatory properties. To optimize its drug properties, identification and development of new kavain-derived compounds was undertaken. A focused library of analogs was synthesized and their effects on Porphyromonas gingivalis (P. gingivalis) elicited inflammation were evaluated in vitro and in vivo. The library contained cyclohexenones (5,5-dimethyl substituted cyclohexenones) substituted with a benzoate derivative at the 3-position of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…However, M101 decreased this exacerbated RANTES response in P. gingivalis-infected EC. Similar trend of results was seen in P. gingivalis-infected macrophages treated with an anti-inflammatory kavain analogue 57 . Moreover, IP-10 release from P. gingivalis-infected EC was down-regulated with M101 treatment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, M101 decreased this exacerbated RANTES response in P. gingivalis-infected EC. Similar trend of results was seen in P. gingivalis-infected macrophages treated with an anti-inflammatory kavain analogue 57 . Moreover, IP-10 release from P. gingivalis-infected EC was down-regulated with M101 treatment.…”
Section: Discussionsupporting
confidence: 83%
“…TRAP assay also demonstrated greater osteoclastic activity in control mice compared to those treated with M101. Similar pattern of reduced inflammation and tissue damage has also been demonstrated using the same model of P. gingivalis -induced subcutaneous calvarial lesion treated with other potential pharmacological therapeutic agents such as miRNA (mmu-miR-155-5p) 89 , anti-inflammatory kavain analogue 57 and probiotic 90 .…”
Section: Discussionsupporting
confidence: 70%
“…Mice were anesthetized by the intraperitoneal injection of ketamine‐xylazine (Akorn Animal Health). The heads of mice were shaved, and P. gingivalis (5 × 10 8 CFU) and A. muciniphila (10 9 CFU) in 100μl of PBS or PBS alone were injected subcutaneously in the four treatment groups with a 30.5‐gauge needle at a point on the midline of the skull between the ears and eyes (Huck et al, , ). Lesions were evaluated each day for 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have optimized the anti-inflammatory potential of kava via medicinal structural modifications of kava compounds. One study evaluated the inhibitory effects of kavain analogs on P. gingivalis-induced inflammation in vitro and in vivo and found that Kava-205Me dose-dependently inhibited TNF-α secretion [ 63 ]. In the same study, Kava-205Me reduced the secretion of other cytokines such as IL-12, eotaxin, RANTES, IL-10 and IFN-γ in murine macrophages.…”
Section: Regulation Of the Inflammatory Responses By Kava And Its mentioning
confidence: 99%